Sinbad goes to sea - Whybrow, Ian (Cambridge : Cambridge University Press, 2016)
Sinbad goes to sea on an adventure. He finds an island - but all is not what it seems. At Turquoise Band descriptions of places and people are extended with literary phrases and expressions which provide new challenges. Vocabulary is often less common and requires the reader to use their knowledge of spelling patterns. Contains full teaching support including learning outcomes, curriculum links and follow-up activities.
Keywords: Children's - stories; Juvenile - works; Fiction